Otoritarianisme dan Dukungan terhadap Demokrasi: Kajian Meta Analisis - Victorius Didik Suryo Hartoko (Faculty of Psychology Universitas Gadjah Mada, 2016)
Authoritarians tend to have submissive attitude toward authority, conservative, and ready to punish groups that have different moral attitudes.These characteristics are not conducive for development of democratic society. This meta-analytical study tries to test relation between authoritarianism and support for democratic values. From 60 articles with 117 studies and 74432 total participants, we found that authoritarianism have negative significant correlation with support for democratic values (Mean effect size=-.3892; p< 0.05). Authoritarianism correlates negatively with support for civic liberty and human rights. Authoritarianism also correlates positively with support for blind nationalism, military interventions,prejudice and discrimination toward groups from different races, immigrants and homosexuals. Authoritarianism can be hindrance for democratization processes.